RESPONSIVITAS KEPOLISIAN DALAM PENANGGULANGAN GENG MOTOR DI KECAMATAN SOMBA OPU KABUPATEN GOWA - Alfian Alfian; Muhammadiah Muhammadiah; Alimuddin Said (Department of Public Administration, Muhammadiyah University of Makassar, 2017)
The objective of this research is to find out the Police Responsiveness towards the Prevention ofMotorcycle Gangs at SombaOpuDistric of Gowa Regency. The type of this research is a qualitativeresearch with case study by describing the police responsivenesstowards the prevention ofmotorcycle gangs at SombaOpu District. The data collection technique was conducted through interview, observation and documentation. The data were analyzed through some steps such as data collection, data reduction, data display and conclusion. For the data validation, the researcher applied triangulation method such as: resource triangulation, technique triangulation, and time triangulation. The results of the research reveal that the Police responsivenesstowards the prevention of motorcycle gangs with 3 indicators are: 1) responsive, 2) fast, and 3) on target. The police have strongly responded to the public complaints related to the motorcycle gangs,yetit is not quite fast or precise in solving motorcycle gang cases. Key word: Responsiveness, prevention, motorcycle gangs ABSTRAK Tujuan Penelitian ini adalah untuk mengetahui bagaimana responsivitas Kepolisian dalam penanggulangan geng motor di Kecamatan Somba Opu Kabupaten Gowa. Jenis penelitian adalah kualitatif dengan menggambarkan responsivitas Kepolisian dalam penanggulangan geng motor di Kecamatan Somba Opu Kabupaten Gowa. Tipe penelitian adalah studi kasus. Dalam pengumpulan data digunakan teknik wawancara, observasi dan dokumentasi. Teknik analisis data menggunakan pengumpulan data, reduksi data, penyajian data dan penarikan kesimpulan. Keabsahan data digunakan triangulasi yaitu triangulasi sumber, triangulasi teknik dan triangulasi waktu. Hasil penelitian menunjukan bahwa responsivitas Kepolisian dalam penanggulangan geng motor dengan indikator 1) Tanggap, 2) Cepat, 3) Tepat. Kepolisian sangat merespon keluhan masyarakat terkait masalah geng motor namun belum begitu cepat maupun tepat dalam menyelesaikan kasus geng motor. Kata kunci : responsivitas, penanggulangan, geng motor